Synthetic studies of swazinecic acid dilactone - Liddell, James Richard (Rhodes University, Faculty of Science, Department of Chemistry, 1989)
The occurrence and syntheses of the pyrrolizidine alkaloids from 1976 to March 1988 is reviewed, and a stereoselective total synthesis of swazinecic acid dilactone was attempted. One approach involved an asymmetric synthesis of the allylic Î±-hydroxy acid 2-hydroxy-2,3-dimethyl-3-butenoic acid employing oxazolines as chiral auxilaries. The oxazoline, (4S,5S)-2-(1-bromoethyl)-4-methoxymethyl-5-phenyl-2-oxazoline, was obtained by direct halogenation of the 2-ethyl oxazoline analogue. This was condensed with acetone in a Darzens type reaction and the resultant epoxy oxazoline rearranged to an allylic Î±-hydroxy oxazoline which was then hydrolysed to the chiral hydroxy acid in low enantiomeric excess. The hydroxy acid, as the O-silylated ethyl ester, was elaborated by allylic diethyl malonate to bromination and condensation with diethyl 5-carboethoxy-2-methyl-3- methylene-2-0-tert-butyldimethylsilylhexanedioate. Removal of the silyl protecting group and epoxidation provided an epoxy triester, which on hydrolysis provided a mixture of acids of uncertain structures.
Keywords: Phrrolizidines; Alkaloids -- Synthesis